2018
DOI: 10.14202/vetworld.2018.1440-1444
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic effect of ursolic acid on Staphylococcal biofilms

Abstract: Aim:The present study was carried out to study the effect of ursolic acid (UA) as a potential anti-biofilm agent in dispersing the biofilm generated by Staphylococcus aureus isolated from milk samples of crossbred dairy cows on the day of drying. Further, in the S. aureus isolates, the presence of intracellular adherence gene locus involved in biofilm production (icaD) was investigated.Materials and Methods:A total of 50 S. aureus strains were isolated over a period of 3 months from 200 milk samples collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…UA can be used synergistically with antibiotics for enhancing their activity [31][32][33] and has proven to be an efficient agent to disperse the biofilm generated by S. aureus [34] and to inhibit the formation of biofilm by MRSA isolates [35]. Although the precise mechanisms underlying these findings are not known in detail, a study on the mode of action of UA against MRSA reported initial irreversible damage to bacterial membrane integrity, UA is considered a promising compound for cancer prevention and therapy, as it influences cell signalling pathways, inhibiting enzyme activity, inducing apoptosis, and reducing tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…UA can be used synergistically with antibiotics for enhancing their activity [31][32][33] and has proven to be an efficient agent to disperse the biofilm generated by S. aureus [34] and to inhibit the formation of biofilm by MRSA isolates [35]. Although the precise mechanisms underlying these findings are not known in detail, a study on the mode of action of UA against MRSA reported initial irreversible damage to bacterial membrane integrity, UA is considered a promising compound for cancer prevention and therapy, as it influences cell signalling pathways, inhibiting enzyme activity, inducing apoptosis, and reducing tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…It suggests that a combination of an antibiofilm agent along with the antibiotics may help to bring the case under control. Jyothi et al (2018) studied the antagonistic effect of UA on S. aureus biofilms using MTP assay and found 71.5% and 48.6% inhibition at UA concentrations of 60 μg/ml and 30 μg/ml respectively, they also showed that the isolates tested to be resistant through antibiotic sensitivity test to commonly used antibiotics were become sensitive to all the tested antibiotics after treatment with UA at both the tested concentrations. The S. uberis isolates treated with UA and resveratrol were more sensitive to antibiotics than untreated.…”
Section: Efficacy Of Resveratrol and Ursolic Acid On Biofilm Inhibiti...mentioning
confidence: 96%
“…Jyothi et al [ 109 ] investigated the antibiofilm activity of UA against 50 S. aureus strains with icaD adhesion gene involved in biofilm production. Inhibition of biofilm formation was observed in 40 isolates of the analysed strains, and it was 48.6% for UA applied at a concentration of 30 mg/L and 71.5% when the UA concentration was 60 mg/L, respectively.…”
Section: Anti-biofilm Properties Of Pentacyclic Triterpenesmentioning
confidence: 99%